Digital Media Ethics of Academic Students at the Indonesian Institute of Education Garut - Nugraha, Yopi; Rahayu, Dinar (Fakultas Kewirausahaan Universitas Garut, 2024)
The development of the digital information has developed rapidly throughout the world, generally in Indonesia, is the result of the rapid development of information and communication technology (ICT), which of course cannot be avoided from these changes, so that without realizing it in human life today This is all about modernization and digitalization. Digital media has become an inseparable part of everyday life, especially for the younger generation who grew up in the digital. PKM activities were held in the Community Service discussion forum workshop with the theme Ethics in Digital Media for IPI Garut students academics. making students become Netiquette pioneers in increasing student awareness in implementing Digital Literacy by understanding digital media ethics in the use of social media, so that it becomes safe and comfortable for students as Netiquette who are aware and responsible in life in cyberspace.